Concept and content of entrepreneurship as an important economic category - Slyuz, Andriy (Global Prosperity, 2022)
The article attempts to clarify the concept and content of entrepreneurship as an important economic category. It is indicated that entrepreneurship as a type of business is an integral element of the state economy. The important role of entrepreneurial activity carried out by economic entities of Ukraine is emphasized and has a significant impact on the filling of the state budget and budgets at the local level, thereby allowing us to strengthen our defense capabilities, which is almost priceless in the conditions of martial law. It was established that entrepreneurship is a strategic factor and an internal source of unstable economic development and material welfare of the country's population in market economic conditions. Having considered separate opinions on the essence and content of the category «entrepreneurship», it was established that its characteristics are primarily based on the state of development of the state's economy, its stability, efficiency and competitiveness, which is achieved, in particular, by using the capabilities of high technologies and innovations. Since entrepreneurship always develops in a certain socio-economic and historical environment, certain prerequisites that contribute to the development of entrepreneurship in Ukraine are highlighted. Such prerequisites include legal, economic, political and psychological. In the context of the analyzed approaches to understanding entrepreneurship, it is noted that the basis of legal prerequisites is state legislation, while the economic prerequisites of entrepreneurship provide for the functioning of multi-entity owners in society. This enables business structures to independently make decisions about the use of property, products, profits, etc.